دور التعليم في سبيل تحقيق أهداف التنمية المستدامة أنموذجا: مواد الاجتماعيات "الجغرافيا والتاريخ" - يونس، منى; قيس، آسيا المهتار (د محمد أمين الضناوي, 2022)
يعد الإنسان محور عملية التنمية المستدامة، التي تتضمن تنمية بشرية قائمة على تحسين مستوى التعليم والثقافة والرعاية الصحية والرفاه الاجتماعي. وقد أشار تقرير اللجنة العالمية للتنمية والبيئة «برونتلاند» إلى أن «التنمية المستدامة هي التنمية التي تلبي احتياجات الحاضر من دون النيل من قدرة الأجيال القادمة على تلبية احتياجاتها» (gov. lbL 28- 2011.(www.lebarmy. كما أن مصطلح تنمية مستدامة تعني عدم الاستهتار والتفريط في مصادر الثروات الطبيعية، التي ترتكز عليها هذه التنمية، أو تدمرها، أي تنمية تعمل على تجديد الموارد والثروات وزيادتها وإعادة التصنيع بشكل يضمن بيئة نظيفة وصالحة لحياة الأجيال الحاضرة والقادمة. أما التعليم فهو عملية اكتساب الفرد المعارف والمعلومات والمهارات المتنوعة بهدف إحداث تغيير في السلوك والمواقف والقيم إضافة إلى توفير فرص عمل، وتحويل الإنسان إلى كائن منتج في المجتمع، مع العلم أن التعليم يساهم في تطوير هذا الكائن، كما أنه يودي دورا مهما في سير عملية التنمية المستدامة، ويحرر الفرد من العبودية والجهل والفقر فما علاقة التعليم بالتنمية؟ ولما كانت الأزمات التي تصيب العالم حاليا على الصعيد الاقتصادي، المالي، الغذائي، التعليمي، ينبغي إيجاد الحلول الممكنة لها عن طريق التربية، فالتعليم يعد الحجر الرئيس في هرم التنمية، وهو الوسيلة الفضلى لاكتساب المعلومات والمهارات لبناء مجتمع يسوده الاستقرار والوعي البيئي ولإعداد موارد بشرية قادرة على إدارة التنمية. The human being is considered the center of the sustainable development process, which includes human development based on improving the level of education, culture, health care and social welfare. The report of the World Commission on Development and Environment “Brundtland” indicated that “sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their needs» (www.lebarmy. gov.lbL28-2011). Also, the term sustainable development It means not disregarding and neglecting the sources of natural resources on which this development is based, or destroyed, i.e. development that works to renew and increase resources and wealth and reindustrialization in a way that ensures a clean and suitable environment for the lives of present and future generations. As for education, it is the process of individual acquiring various knowledge, information and skills with the aim of bringing about a change in behaviour, attitudes and values. In addition to providing job opportunities, and transforming man into a productive being in society, knowing that education contributes to the development of this organism, as it plays an important role in the progress of the process Sustainable development, liberating the individual from slavery, ignorance and poverty. What is the relationship between education and development? Since the crises currently afflicting the world at the economic, financial, nutritional, educational level..., possible solutions should be found through education. Education is the main stone in the development pyramid, and it is the best way to acquire information and skills to build a stable society and environmental awareness and to prepare Human resources capable of managing development.
Keywords: التنمية المستدامة -- التعليم اللبناني -- المواد الاجتماعية -- التنمية البشرية